Solving the Mystery of African Governance - Lin, Justin Yifu (Taylor and Francis, 2013)
The dominant view of good governance as a pre-condition for economic success is theoretically compelling but empirically difficult to establish. Historical analyses tend to indicate a very strong correlation between institutional development and economic growth. Today’s high-income and good-governance countries generally had bad-governance environments at low levels of income. Moreover, some of today’s most successful economies still exhibit sub-optimal governance indicators. By focusing on the search for the determinants of some global governance standards that often reflect particular political, ideological and philosophical conceptions of power, the traditional literature on governance has so far failed to offer a set of actionable policies that poor countries could implement to foster inclusive growth in a pragmatic and incentives-compatible way. This article acknowledges that governance problems are indeed major impediments to economic growth. But contrary to conventional wisdom, it argues that the well-known governance problems in African countries are mainly the reflection of their low level of development, and the results of failed state interventions and distortions originating from erroneous economic development strategies. Instead of posing ‘good’ governance as the main prescription and a prerequisite for sustained growth, development economists should design policy frameworks that offer the maximum likelihood of success because they are consistent with comparative advantage while providing minimum opportunities for rent-seeking and state capture.